Electrolysis applied for simulated textile effluents degradation containing acid red 151 and acid blue 40 - Sousa, Mariana Lopes de [UNESP]; Bidoia, Ederio Dino [UNESP] (Springer, 2014)
Textile industry is responsible for a large amount of polluted water released daily, mainly due to the dyes used. This article has aimed to study and improve methodologies for degrading textile effluents containing the dyes Acid Red 151 and Acid Blue 40 using an electrolytic reactor. Different solutions were prepared for the experiments in the electrolytic reactor with a 70 % TiO2/30 % RuO2 anode. The textile effluents underwent 0 (control), 3, and 30 min treatment intervals. A suspension of Saccharomyces cerevisiae cells was used for toxicity tests and performed at the same day that samples were collected. The same test was applied to the samples after 15 days resting in order to verify changes in toxicity. The electrolytic treatment successfully removed the color in all effluents. However, the process efficiency varies according to the dye used and the experimental conditions, such as current and NaCl concentration. Also, it was observed that treatments longer than 30 min are very toxic to S. cerevisiae cells because of the high concentration of Cl-2.
Keywords: Textile dye; Toxicity; Effluent; S. cerevisiae